2023
DOI: 10.1101/2023.02.21.526496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Markerless motion capture estimates of lower extremity kinematics and kinetics are comparable to marker-based across 8 movements

Abstract: Motion analysis is essential for assessing in-vivo human biomechanics. Marker-based motion capture is the standard to analyze human motion, but the inherent inaccuracy and practical challenges limit its utility in large-scale and real-world applications. Markerless motion capture has shown promise to overcome these practical barriers. However, its fidelity in quantifying joint kinematics and kinetics has not been verified across multiple common human movements. In this study, we concurrently captured marker-ba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…A markerless prenium system was chosen in the present study; it has been shown to provide data on lower limbs gait kinematics that are as reliable as those from marker-based systems, as revealed by the inter-session variability, inter-trial variability and inter-session variability ratios [24]. Estimates from this markerless motion capture system were also very similar to those obtained from marker-based motion capture in terms of ankle and knee joint angles and moments [23,29]. This system only requires calibration of the area captured by the cameras.…”
Section: Discussionmentioning
confidence: 82%
“…A markerless prenium system was chosen in the present study; it has been shown to provide data on lower limbs gait kinematics that are as reliable as those from marker-based systems, as revealed by the inter-session variability, inter-trial variability and inter-session variability ratios [24]. Estimates from this markerless motion capture system were also very similar to those obtained from marker-based motion capture in terms of ankle and knee joint angles and moments [23,29]. This system only requires calibration of the area captured by the cameras.…”
Section: Discussionmentioning
confidence: 82%
“…Infrared-re ective markers were placed on the participants' lateral trochanters, toe, menisci, heel, malleoli, and an additional marker was placed on the individuals' sternum for ease of marker calibration during gait analysis. These marker placements allow processing of lower limb joint kinematics along with spatiotemporal gait analysis in the sagittal plane, and it is also consistent with a subset of the CAREN system's HBM lower body model [50,51,52]. Eleven infrared-re ective markers were placed at locations indicated with red circular dots: lateral trochanter, lateral malleoli, menisci, heel, toe, and bottom of the sternum.…”
Section: Methodsmentioning
confidence: 79%
“…The results demonstrated a significant improvement in scene initialization and infant motion tracking; however, artifacts were still noticeable in the reconstruction, partly due to imperfect segmentation masks. In contrast to [33], [34] analyzed crucial movements to assess in-vivo human biomechanics using the Markerless motion capture system assisted by Microsoft Kinect. In this system, the camera has depth and infrared sensors to track body movements without the need for physical markers.…”
Section: ) Markerless Motion Capturementioning
confidence: 99%